The individual accountability issue in portuguese public health (Brazilian Journal of Health Research, 2019)
Introduction: Health prevention is the main theme of the World Health Organization (WHO). It has been applied to public health actions in all countries of the European Union, including Portugal, for many decades now. Objective: Discussing the social and individual accountability issue in the current Public Health scenario in Portugal due to a political proposal to likely abandon the shared accountability model applied to public health. Methods: The study addresses the social and health status verified over the last decades in Europe, mainly in Portugal. It discusses Ethics and public health, as well as actions focusing on the intersection among Risks, Health Effects and Prevention. The discussion distinguishes individual from social accountability, which is a subject that emerges from the values that guide, or that should guide, humans’ relationships to each other, debates, justice and the right to health, based on the reality of healthcare in Portugal. The prioritization of financial resources seems to be an ethical dilemma for Portuguese decision-makers. Results: The current situation of public finances, mainly in Portugal, should imply the search for new perspectives, according to which, the participation of all health agents - in particular doctors, nurses and other technicians -, becomes indispensable. They must address their positions about the ways through which they aim at exercising their professional activity based on clear definitions about rights and duties. Conclusion: The State must commit to health professionals in order to establish political, financial and clinical principles to achieve an efficient and effective health plan.